Authenticity framing and market creation for meta organisations: The case of the Swartland Independent Producers in the South African wine field - Steyn, Jonathan Daniel (Graduate School of Business (GSB), 2022)
This PhD thesis studies the Swartland Independent Producers (SIP) meta-organisation, located in the Western Cape wine region of South Africa, and asks: how and why the collective rendering of authenticity creates markets? Seventy-one interviews were realised with producers making “authentic wine” and other market participants active in the South African wine industry between 2010 and 2016. How and why businesses create markets by rendering authenticity through collective action organised within meta-organisations has not been fully explored in the organisational authenticity literature. The framework developed through a qualitative analysis of the SIP case, contributes to filling this gap by showing that authenticity can be constructed, and new markets created for meta-organisations, via the interplay of two sets of intersecting meta-framings: authenticity work and authentication work, and hot and cool authenticity framing. This thesis demonstrates that authenticity work may comprise three meso-framings: claiming purity, performing charisma and meta-organisational tethering. Simultaneously, this study conceptualises how market participants purposively engage in authentication work through meso-framings of polarising evaluation, valorising status, and reframing meaning. The theoretical framework refines the current scholarly explanation of why rendered authenticity creates markets. By bridging the sociology and organisational literatures dedicated to authenticity, this PhD developed four novel authenticity meta-framing constructs: hot and cool authenticity work and hot and cool authentication work. Through further theorising their interactions, this study advances current academic knowledge on how and why rendering authenticity is a central concern for businesses intending to create markets through meta-organisational collective action.